The Triple Impact of Innovation, Financial Inclusion and Renewable Energy Consumption on Environmental Quality in Some Emerging Economies - Kaplan, Muhittin; Rahman, Mohammed Muntaka Abdul; Khan, Asad-ul-Islam; Vergil, Hasan (International Journal of Energy Economics and Policy, 2024)
This paper investigates the triple impact of innovation, financial inclusion, and renewable energy consumption on the quality of the environment. The study employed data between 2007 and 2019 from selected emerging economies. Using the fixed effect, two-step GMM econometric method. The result found that financial inclusion and innovation have a positive relationship with carbon emissions, hence contributing to the reduction in the quality of the environment. Renewable energy consumption was found to reduce carbon emissions. Similarly, the interactive terms TPT*FIN, FIN*REN, and TPT*REN were all negatively related to carbon emissions. The study recommends that governments should increase financial instruments to support innovation that will enhance environmental quality. Additionally, governments should strengthen their environmental policies. Financial institutions should encourage firms to access green finance solutions. The value and originality of this study is the introduction of the interactive term, which throws more light on variables that affect the environment and through which channels. Moreso, there are few works with these interactive terms relative to emerging economies. Third, there are no previous studies that employed the fixed effect two-step GMM to analyze the impact of financial inclusion, technological innovation, and renewable energy consumption on environmental quality.